REPRESENTASI TRADISI BONOKELING DALAM RUANG DIGITAL: STUDI ETNOGRAFI DIGITAL - Iqbal Yulianto; Wasino Wasino; Tri Astuti; Argitha Aricindy; Lulu’ Arifatun (Jurnal Ilmiah Multidisiplin Ilmu, 2026)
This study aims to analyze the representation of Bonokeling traditions in the digital space and to examine the opportunities and challenges faced by the indigenous community in the process of cultural digitalization amid the growing influence of information technology on cultural practices and interactions. This research employs a qualitative approach using a digital ethnography method. Data were collected through online participant observation, in-depth interviews with customary leaders, youth, and community social media managers, digital documentation, and a literature review. Data analysis was conducted using an interactive model through the stages of data reduction, data display, and conclusion drawing, and employed visual and narrative discourse analysis. The results show that the representation of Bonokeling traditions in the digital space is dominated by the visualization of rituals, traditional symbols, and the daily activities of the community. The digital space is interpreted as a medium for cultural preservation and a means of strengthening cultural identity, particularly among the younger generation. However, digitalization also gives rise to challenges such as the reduction of sacred meaning, the commodification of tradition, and identity negotiation between customary values and the logic of modernity. This study emphasizes the importance of managing cultural representation wisely to ensure that the digitalization of tradition remains grounded in local wisdom values